Peripheral and central effects of intracerebroventricular microinjection of Hottentotta gentili (Pallary, 1924) (Scorpiones, Buthidae) venom. (1st March 2016) - El Hidan, Moulay Abdelmonaim; Touloun, Oulaid; El Hiba, Omar; Laadraoui, Jawad; Ferehan, Hind; Boumezzough, Ali
Abstract: Central effects of scorpion venom toxins have been neglected, due both to the common belief that scorpion venoms act by targeting peripheral organs and also to the misunderstanding that these peptides do not cross the brain-blood barrier (BBB). Determining whether scorpion neurotoxicity is restricted to peripheral actions or whether a central mechanism may be partly responsible for systemic manifestations could be crucial in clinical therapy trends. The present study therefore aims to assess histopathological damages in some organs (heart, kidney, liver, and lungs) and the related biochemical impairments, together with a neurobehavioral investigation following an intracerebroventricular (i.c.v) micro-injection of Hottentotta gentili (Scorpiones, Buthidae) venom (0.47 μg/kg). I.c.v. injection of venom produced focal fragmentation of myocardial fibers, while lungs showed rupture of the alveolar structure. Concurrently, there was a significant rise in the serum enzymes levels of ASAT, ALAT, CPK and LDH. Meanwhile, we observed behavioral alterations such as a hypoactivity, and in addition the venom seems to have a marked anxiogenic-like effect. The present investigation has brought new experimental evidence of a peripheral impact of central administration of H . gentili venom, such impact was manifested by physiological and behavioral disturbances, the last of these appearing to reflect profound neuro-modulatory action of H . gentili venom. Highlights: ICV injection of H . gentili venom induces histological changes in heart and lungs. ICV injection of H . gentili venom induces an increase in AST, ALT & LDH activities. ICV H . gentili venom induces an anxiety-like behavior.